(untitled) (Medico Legal Update, 2020)
Software industry is a human capital intensive industry. A study was conducted to assess mental health among IT professionals. The objectives were 1). To assess the mental health among IT profession and 2). To find out the association between IT profession’s mental health and their selected demographic variables. Majority of the clients who scored positive for social dysfunction, anxiety & depression and loss of confidence were between 20-30 years of age, females, software engineers, had undergraduate education, had total work experience in software between 4-7 years and in the current company, followed Hindu religion, were married, residing in urban locality and had job satisfaction. Age and experience in the current company were associated with anxiety and depression.